4CPS-129 Pilot study to survey the attitude, supplement use and storage conditions of drug products among patients receiving biological therapy. (24th March 2020) - Vida, RG; Somogyi-Végh, A; Mayer, M; Kiss, D; Schaadt, N; Rajj, R; Molnár, B; Botz, L
Abstract : Background and importance: Biological therapies have recently become the cornerstone for the treatment of several dermatological and rheumatological diseases. As compensation for the extra workload associated with it, the system of itemised reimbursement of these products provides hospital pharmacists with a deeper insight and closer involvement in the therapy. Aim and objectives: Our aim was to assess the factors potentially affecting the effectiveness and safety of the therapy, and to become familiar with patient opinions on the drug supply, current form of dispensing and information received. Material and methods: Data were collected through structured personal interviews and review of the medical records. Twenty-six dermatological and 37 rheumatological patients were interviewed at the point of dispensing of the biologics. The survey focused on concomitant drugs and supplementary products (dietary supplements, herbal remedies, etc), patient opinions, and experience and knowledge of biological therapy. In the case of an additional 28 participants, storage conditions at the patients' homes were assessed with a Testo 184 T3 temperature data logger. Results: The 32 women and 31 men who completed the survey had been receiving biological therapy for an average of 6.5 years. There was a switch between biological agents in 21 patients and therapy had been changed twice in 10 patients. The average number of prescribed medicines and supplementary products were 6.6 (1–24) and 2.3 (1–8), respectively. A total of 33 patients (52.4%) used at least one supplementary product. We identified two main topics that patients wanted more information on: side effects and available alternatives in the event of therapeutic failure. Of 28 temperature logs, only 3 remained between 2 and 8°C. Conclusion and relevance: Biological therapies have revolutionised the clinical care of many diseases but because of their costs, it is essential to identify factors that influence therapeutic outcomes. Also, hospital and clinical pharmacists have the opportunity and competence to contribute to the optimisation of therapy. As data on home storage conditions, drug–drug and drug–supplement interactions with monoclonal antibodies are lacking, this pilot study can be the first step towards understanding the importance of these factors and their effect on the safety and effectiveness of the therapy. References and/or acknowledgements: No conflict of interest.